PLATELET-RICH AUTOPLASMA IN SURGICAL TREATMENT OF DEGENERATIVE DYSTROPHYC TENDOMUSCULAR LESIONS - Панов, Алексей Александрович (Medicine in Kuzbass, 2018)
Objective: using of superelastic nikelide titan implants,titan anchors and platelet-rich autoplasma in degenerative dystrophic tendomuscular lesions.Methods – age and gender composition of patient groups, early postoperative period clinical observation, estimation of long-term postoperative results, comparison of postoperative results in degenerative dystrophic tendomuscular lesion surgical treatment using platelet-rich plasma and without it.Results. Age and gender composition in groups of patients with degenerative dystrophic tendomuscular lesions of distal biceps tendon, knee extensor apparatus and calf triceps were researched. Clinical observations of early postoperative period in tendoplasty, using titan anchors and superelastic titan nikelide implants in combination with platelet-rich autoplasma and separately were performed. Long-term postoperative results according to functional scales were estimated. Early and long-term treatment results are compared with the methods of descriptive statistics and by the criterion T.Conclusions. 1. Difference of age and gender composition in basic and control groups of patient with degenerative dystrophic lesions has no statistical significance. Results of research could be comparabe. 2. Early postoperative results in clinical observations has no statistically significant difference between patients of basic and control groups. 3. Long-term postoperative results of surgical treatment are more successful in common group, than in control. A difference of results after 12 and 24 months is statistically significant.
Keywords: degenerative dystrophic lesion; tendomuscular complex; platelet-rich auto plasma; superelastic titan nikelide implants; anchor